Diagnostic Value of RDW-Albumin Ratio for the Prediction of Mortality in Sepsis Associated Nonthyroidal Illness Syndrome Patients: A Retrospective Cohort Study - Zhang J; Xu P; Huang Y; Li J; Ma C; Liu G; Ye J; Guo Y; Feng Z; Jiang B; Pan S; Gao C (Journal of Inflammation Research)
Jiyuan Zhang,1,* Peixian Xu,1,* Yingying Huang,1,* Juan Li,1 Chaoping Ma,1 Guoxiang Liu,1 Jiawei Ye,1 Yiran Guo,1 Zhihui Feng,1 Bojie Jiang,1 Shuming Pan,1,2 Chengjin Gao1 1The Department of Emergency, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Shanghai Putuo District Hospital, Shanghai, 200062, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chengjin Gao; Shuming Pan, Email gaochengjin@xinhuamed.com.cn; panshuming1103@163.comBackground: The correlation between RAR is linked to negative outcomes in sepsis, but it remains uncertain if RAR is connected to prognosis in patients with sepsis-related NTIS. So we investigated it in this study.Methods: Patients with sepsis-associated NTIS admitted to Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, between March 2013 and April 2017 were included in the study. Participants were divided into two groups according to the optimal threshold value for RAR determined by the receiver operating characteristic curve. Cox proportional hazards regression and graphed with Kaplan–Meier curves examined the relationship between RAR and survival in patients with sepsis-associated NTIS. To account for potential confounding variables, a propensity score matching method was conducted to verify the relationship. Subgroup analysis was performed for different sex, age, comorbidities, infection location and other scores.Results: A total of 328 patients with sepsis-related NTIS were analyzed in our study. The univariate and multivariate regression analysis indicated that RAR was a significant risk factor for 30-day mortality (HR 1.039(1.012, 1.067), p = 0.004). However, subgroup analysis suggested that RAR may not be an independent risk factor for 30-day mortality in sepsis patients with NTIS combined with tumor or urogenital infection. ROC analysis demonstrated that RAR had a high discriminatory ability for predicting 30-day mortality (AUC 0.751, p < 0.001). Kaplan-Meier curve analysis indicated increased 30-day mortality in the higher RAR group. Following PSM, 108 pairs of patients with matched scores were created. The multivariate regression model demonstrated that RAR was an independent factor associated with 30-day mortality risk (HR 1.049 (1.015, 1.085), p = 0.005). ROC analysis revealed that RAR was a strong discriminator for the 30d-mortality (AUC: 0.695, 95% CI: (0.598– 0.792)).Conclusion: A strong correlation was found between RAR and unfavorable clinical results in sepsis-related NTIS, where a greater RAR was linked to increased 30-day and in-hospital death rates.Keywords: sepsis, red blood cell distribution width, albumin, nonthyroidal illness syndrome, prognosis